Impact of Aeromonas and diarrheagenic Escherichia coli screening in patients with diarrhea in Paraná, southern Brazil - Assis, Flávia E.A.; Wolf, Suélen; Surek, Monica; De Toni, Fabiana; Souza, Emanuel M; Pedrosa, Fábio O; Farah, Sônia M. S. S.; Picheth, Geraldo; Fadel-Picheth, Cyntia M.T. (The Journal of Infection in Developing Countries, 2014)
Introduction: A wide diversity of bacterial agents may cause diarrhea, presenting challenges to clinical laboratories to define a diagnosis. Considering that most stool cultures are negative, we screened stool samples from patients with diarrhea for the presence of 14 bacterial enteropathogens, aiming to establish which of them should be included in routine stool analysis. Methodology: Stool samples from 400 patients with diarrhea were analyzed for the presence of Salmonella, Shigella, Campylobacter, Aeromonas, Plesiomonas shigelloides, Vibrio, Yersinia enterocolitica, and diarrheagenic Escherichia coli using conventional microbiological methods and PCR. Two distinct samples were studied; one included predominantly patients involved in outbreaks, and the other patients of low socioeconomic status presenting sporadic cases of diarrhea. Results: In total, 86 cultures (21.5%) were positive. Mixed infections were found in five patients, leading to recovery of 91 strains of enteropathogenic bacteria: Salmonella Enteritidis (9.2%), Aeromonas (7.2%), diarrheagenic E. coli (5.2%), and C. jejuni (1%). However, Salmonella predominated, with 11.5% frequency in diarrhea outbreaks, while Aeromonas predominated among patients of low socioeconomic status, with 14.6% frequency. Conclusion: Aeromonas and diarrheagenic E. coli, which are not routinely screened for, deserve to be included in laboratory screening panels.